EDUCATION ON PREVENTING NECK PAIN CAUSED BY INCORRECT SLEEPING POSITIONS AMONG STUDENTS AT PAWYATAN DAHA 1 JUNIOR HIGH SCHOOL IN KEDIRI CITY: EDUKASI PENCEGAHAN NYERI LEHER AKIBAT POSISI TIDUR YANG TIDAK TEPAT PADA SISWA SMP PAWYATAN DAHA 1 KOTA KEDIRI. - Zhara Fatima Nasta'in; Barreta Bintang Sadewa; Cindy Putri Aryani; Elvina Riski Mufidah; Iqbal Taufiqurrahman Alfiandy (PT. ROCE WISDOM ACEH, 2026)
Neck pain is a common complaint and can be triggered by various factors, including improper sleeping positions and the use of unsuitable pillows. Non-ergonomic sleeping positions can cause neck muscle tension, cervical bone disorders, and excessive pressure on the sternocleidomastoid muscles, leading to stiffness, limited movement, and pain. This community service activity aims to assess respondents’ understanding of how to prevent neck pain caused by improper sleeping positions after receiving health education. This community service used a quantitative descriptive design with 26 respondents from class 7C of SMP Pawyatan Daha 1 Kediri, conducted on 10 November 2025. Data were collected through a post-test questionnaire containing 10 statements, using a four-point Likert scale, covering aspects of understanding neck pain, improper sleeping positions, appropriate pillow use, and stretching. The education was delivered using leaflets and PowerPoint presentations as supporting materials. Data were analyzed using quantitative descriptive methods to assess respondents’ understanding after the education session. The study found that the average overall score for respondents was 30.77, with a range of 20-38 and a standard deviation of 4.179, indicating an increase in knowledge in the high category. The conclusion of this study indicates that health education through leaflets and demonstrations successfully improved students’ understanding of how to prevent neck pain caused by improper sleeping positions. Further research is recommended using a pre-test and post-test design to more comprehensively measure the effectiveness of the intervention.